Tourism in Protected Natural Areas - Denkewicz , Patricia; Pimentel , Juliana Maria Vaz (Seven Editora, 2023)
It is relevant to seek to understand this phenomenon which is the evasion in Distance Education, because, within the public university, it constitutes a waste of public resources and, as far as the PNAP makes it impossible to achieve its purpose in its entirety, as well as, demonstrates the student’s disengagement in obtaining excellence in the public sector. The aim of this study was to describe and analyze the evasion through the profile of students (measured by gender dimensions, academic education in undergraduate, public service time and chronological age) in relation to the specialization course in Public Management - class 3 - of the National Program for the Formation of Public Administration (PNAP), offered by the State University of Maringá (UEM), PR. Therefore, a descriptive and quantitative research was conducted, with secondary data (documentary and bibliographic research), content analysis was used that through systematic procedures, objectives of organizing the data with indicators of have allowed the inference of knowledge on the subject. The results showed that there was a significant rate of evasion in the course, with emphasis on the number of dropouts in all poles. It is concluded that the evasion in the course /PNAP is a challenge that should integrate the UAB, the university and the face-to-face centers, with policies, strategies and actions to contain evasion, which involve quantitative and qualitative aspects aiming at excellence in public management, in addition to raising the student’s awareness of his co-responsibility in this result. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-154